Constraints on the origin of cosmic rays above $10^{18}$ eV from large scale anisotropy searches in data of the Pierre Auger Observatory - Collaboration, PA (2012)
A thorough search for large scale anisotropies in the distribution of arrival directions of cosmic rays detected above $10^{18}$ eV at the Pierre Auger Observatory is reported. For the first time, these large scale anisotropy searches are performed as a function of both the right ascension and the declination and expressed in terms of dipole and quadrupole moments. Within the systematic uncertainties, no significant deviation from isotropy is revealed. Upper limits on dipole and quadrupole amplitudes are derived under the hypothesis that any cosmic ray anisotropy is dominated by such moments in this energy range. These upper limits provide constraints on the production of cosmic rays above $10^{18}$ eV, since they allow us to challenge an origin from stationary galactic sources densely distributed in the galactic disk and emitting predominantly light particles in all directions.